Effective Low-Level Laser Therapy Including Laser Acupuncture Treatment Conditions for Non-Specific Chronic Low Back Pain: Systematic Review and Meta-Analysis - Hyewon Yeum; Yejin Hong; Dongwoo Nam (MEDrang Inc., 2021)
Low-level laser therapy including laser acupuncture has been widely used for non-specific chronic low back pain in primary Korean medical clinics. However, there is no critically appraised data regarding which treatment conditions are most effective. A systematic review and meta-analysis was conducted to determine effective treatment conditions using 12 databases (PubMed, Ovid, CENTRAL, KoreaMed, KMBASE, KISS, NDSL, KISTI, OASIS, CNKI, CiNII, and J-STAGE). There were 1,019 studies retrieved and 13 studies included in this review. It was determined that when the power output was ≥ 50 mW, the beam size was increased to ≥ 1 cm2, the energy dose was increased to ≥ 4 J per point, the treatment interval was increased to ≥ 3 times a week, and the number of treatment sessions was increased to ≥ 10 treatments, these conditions appeared to increased treatment effectiveness.